Development Communication Efforts by the Government of Eureunpalay Village, Cibalong Subdistrict, Tasikmalaya, in Addressing Unemployment - Pradhana, Yudha; Dinar Kadarsih (International Journal of Environmental Communication (ENVICOMM), 2025)
Unemployment is one of the primary issues in Eureunpalay Village, Cibalong Subdistrict, Tasikmalaya. Low education levels, limited access to skills training, and a lack of economic opportunities are the main contributing factors. The Eureunpalay Village Government implements development communication strategies to address unemployment through participatory and inclusive approaches. This study aims to analyze the development communication efforts carried out by the village government in tackling the unemployment problem. The research employs a descriptive qualitative approach with data collection techniques including observation, in-depth interviews, and document analysis. The results indicate that development communication is conducted through various strategies, such as village deliberations, utilization of social media, and community economic empowerment programs. The village government actively socializes programs such as cash-for-work initiatives, skills training, and the development of agrotourism-based village tourism in Pasir Hantap. Moreover, open and collaborative communication between the village government, the Village Consultative Body (BPD), and the community contributes significantly to the effectiveness of the implemented programs. The study concludes that effective development communication can enhance community involvement in efforts to reduce unemployment. Therefore, it is necessary to optimize village communication media, strengthen the communication capacity of village officials, and conduct regular evaluations of the communication strategies applied.